Chapter Dal Filostrato ai rispetti di ambiente laurenziano: la ricezione quattrocentesca della prima lettera di Troiolo a Criseida - Litterio, Silvia (Studi e saggi, 2020)
The article informs that some octaves of Boccaccio's Filostrato can be found since the turn of the 14th century as a single Rispetto d'amore or in series of Rispetti continuati or even under the title Canzona. Boccaccio's ottava rimas were used as love Rispetti both in manuscripts and in incunabula: the article gives an index and a description of them.